2008
DOI: 10.1105/tpc.107.056119
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsisPhosphatidylinositol Phosphate 5-Kinase PIP5K3 Is a Key Regulator of Root Hair Tip Growth

Abstract: Phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] functions as a site-specific signal on membranes to promote cytoskeletal reorganization and membrane trafficking. Localization of PtdIns(4,5)P 2 to apices of growing root hairs and pollen tubes suggests that it plays an important role in tip growth. However, its regulation and mode of action remain unclear. We found that Arabidopsis thaliana PIP5K3 (for Phosphatidylinositol Phosphate 5-Kinase 3) encodes a phosphatidylinositol 4-phosphate 5-kinase, a key e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(230 citation statements)
references
References 61 publications
11
216
1
2
Order By: Relevance
“…In mammalian systems, GAP activity of the AZAP-type ARF-GAPs is stimulated by phosphoinositide binding to the PH domain (Jackson et al, 2000). In this regard, overexpression or down-regulation of a type B phosphatidylinositol-4-phosphate 5-kinase 3, which regulates endogenous phosphatidylinositol-4,5-bisphosphate levels, leads to deformed root hairs (Kusano et al, 2008;Stenzel et al, 2008). Further support for the interdependence of lipid signaling and small GTPases in root hair growth comes from the observation that RabA4b recruits phosphatidyl 4-OH kinase to the growing root hair tip and that knockouts of this gene induced the formation of wavy root hairs similar to agd1 (Preuss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian systems, GAP activity of the AZAP-type ARF-GAPs is stimulated by phosphoinositide binding to the PH domain (Jackson et al, 2000). In this regard, overexpression or down-regulation of a type B phosphatidylinositol-4-phosphate 5-kinase 3, which regulates endogenous phosphatidylinositol-4,5-bisphosphate levels, leads to deformed root hairs (Kusano et al, 2008;Stenzel et al, 2008). Further support for the interdependence of lipid signaling and small GTPases in root hair growth comes from the observation that RabA4b recruits phosphatidyl 4-OH kinase to the growing root hair tip and that knockouts of this gene induced the formation of wavy root hairs similar to agd1 (Preuss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, disrupted F-actin dynamics could interfere with the tip recruitment of lipid signaling components that bind to actin, such as phosphatidylinositol phosphate kinase 1 (Davis et al, 2007) or trafficking of RHD2, the ROS-generating NADPH oxidase, which was recently shown to be dependent on actin for proper root hair tip localization (Takeda et al, 2008). As alterations in the metabolism of phosphoinositide lipid mediators have been shown to affect root hair growth (Bohme et al, 2004;Vincent et al, 2005;Kusano et al, 2008;Stenzel et al, 2008;Thole et al, 2008), the disruption of apical F-actin dynamics at the root hair tip, regardless of whether it is a direct result of the loss of AGD1 function, continues to point to an elaborate system of feedback regulation between lipids, small GTPases, and the cytoskeleton in the maintenance of tip growth (Nibau et al, 2006;Kost, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The amplified amiRNA fragment was then introduced into the pER8 vector to generate FAB1A/B-amiRNA/pER8. The transgenic plant conditionally expressing GFP (ER8-GFP) was used as a mock control (Kusano et al, 2008). Constructed plasmids and generating transgenic plants used in this study are listed in Supplemental Table S1.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…The catalytic activities of using PtdIns4P as the preferred substrate to generate PtdIns(4,5)P 2 have all been characterized [15][16][17][18]. Studies have revealed the physiological functions of some PIP5Ks, including PIP5K1 in abscisic acid signaling [19]; PIP5K3 in root hair formation and growth [16,20]; PIP5K4 in stomata opening [21]; and PIP5K4-6 in pollen tube growth [17,22]. In addition, PIP5K9 regulates root growth and is involved in sugar signaling [23].…”
Section: Introductionmentioning
confidence: 99%